2015 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS) 2015
DOI: 10.1109/iros.2015.7354239
|View full text |Cite
|
Sign up to set email alerts
|

Path tracking by a mobile robot equipped with only a downward facing camera

Abstract: Abstract-This paper presents a practical path-tracking method for a mobile robot with only a downward camera facing the passage plane. A unique algorithm for tracking and searching ground images with natural texture is used to localize the robot without a feature-point extraction scheme commonly used in other visual odometry methods. In our tracking algorithm, groups of reference pixels are used to detect the relative translation and rotation between frames. Furthermore, a reference pixel group of another shap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…x and v (f ) y respectively, and when the angle of rotation during the rotary motion is defined as θ (f ) , the keypoint's movement position of X-axis and Y-axis, x (f +1) and y (f +1) can be calculated from equation (2).…”
Section: B Akaze Feature Matching With Estimation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…x and v (f ) y respectively, and when the angle of rotation during the rotary motion is defined as θ (f ) , the keypoint's movement position of X-axis and Y-axis, x (f +1) and y (f +1) can be calculated from equation (2).…”
Section: B Akaze Feature Matching With Estimation Methodsmentioning
confidence: 99%
“…of template matching methods applied in self-localization are Nagai's downward facing camera method [2], Savan's ground vehicle method [3] and Andrew's real-time stereo visual odometry method [4]. However, the method using template matching needs to control the illumination of light.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has some advantages over approaches using forward-facing cameras: it does not have any issues with occlusions of the surrounding, it works in environments without static landmarks, and it can be made independent of the surrounding lighting. Previous work has shown that reliable high-accuracy pose estimates can be achieved with ground texture based localization on typical ground texture types, such as asphalt and concrete [3], [4], [5], [6], [11], [13], [16].…”
Section: Introductionmentioning
confidence: 99%
“…Visual odometry for mobile robots and automobiles has been recently developed using downwardfacing standard cameras [32][33][34][35][36] and optical mice [37][38][39], as well as custom-made OF sensors [40,41], since the visual patterns and light conditions encountered in this way are relatively uniform, and the distance between the sensors and the ground usually changes slightly. In most cases, the authors used the car-like non-holonomic constraint to estimate the vehicle's position and orientation using simple methods involving low computational costs.…”
Section: Introductionmentioning
confidence: 99%
“…However, solutions based on standard cameras [33,36] still fail to cope with high-dynamic-range lighting conditions, as well as being impeded by the low frame rate and the high computational cost of the image processing: only a narrow range of low velocity measurements can often be obtained using this approach.…”
Section: Introductionmentioning
confidence: 99%